Ideo method cards : 51 ways to inspire design. (S.l. : IDEO)
IDEO Method Cards show 51 of the methods we use to inspire great design and keep people at the center of our design process. Each card describes one method and includes a brief story about how and when to use it. The cards are divided into four categories: Learn, Look, Ask and Try, making it easy to reference, browse, sort, and share the cards. Created in response to requests from clients, colleagues, students, and teachers, the Method Cards are intended as inspiration for practicing and aspiring designers, as well as those seeking a creative spark in their work. It's a design tool meant to help you explore new approaches and develop your own. Use the deck to take a new view, to inspire creativity, to communicate with your team, or to turn a corner.
Keywords: Inspireren; Design; Gezelschapsspellen; Kaartspellen